Education Pengaruh Model Pembelajaran Rms Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Virus - Yanwar Habibul Muttaqin; Nisa Sholehah Pangsuma; Sri Hartati; Asrianty Mas’ud (Pusat Riset dan Inovasi Nasional, 2023)
This research is based on a problem found in one of the Madrasah Aliyah schools, namely the model used is not diverse enough that it is considered boring. When learning accepts students feel bored and bored. So that learning activities in class tend to be more rigid and passive. The purpose of this study was to analyze students' responses to the model. learning RMS (Reading, Mind mapping, and Sharing) on ​​Virus material. The research method used is Quasi Experimental (Quasi Experimental). Obtaining data in this study showed that the average student response was 77% in the good category. Thus it can be concluded that students' responses to the RMS learning model (Reading, Mind mapping, and Sharing) on ​​Virus material can be used because it is more fun so it can be used as an alternative. Students are expected to have the same opportunity to develop, and it is recommended that research is conducted to examine more deeply. more about student responses. against models. RMS learning (Reading, Mind mapping, and Sharing) on ​​other Virus materials.